2005
DOI: 10.1002/pca.817
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC determination of vasicine and vasicinone inAdhatoda vasica

Abstract: A simple high-performance thin-layer chromatographic (HPTLC) method has been developed for the simultaneous determination of the pharmacologically important quinazoline alkaloids vasicine and vasicinone in Adhatoda vasica. The assay combines the separation and quantification of the analytes on silica gel 60 GF254 HPTLC plates with visualisation under UV and scanning at 270 and 281 nm. Using this technique, the alkaloidal content of different parts of the title plant have been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…It was noteworthy to mention that the vasicinone quantity from the in vitro leaves was almost 2.5-fold higher than its in vivo counterpart. An earlier study (Das et al 2005 ) reported that the vasicinone production in leaves (in vivo) was higher (0.047%; w/w ) in comparison to stem (in vivo) (0.027%; w/w ) of A. vasica , which supports our results where we found leaf samples to be the superior choice for vasicinone extraction than the other plant parts. Significant variation in vasicinone content was observed among in vitro leaf, callus and in vivo leaf; nonetheless, in vitro stem and in vivo stems yielded comparable quantities of vasicinone.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It was noteworthy to mention that the vasicinone quantity from the in vitro leaves was almost 2.5-fold higher than its in vivo counterpart. An earlier study (Das et al 2005 ) reported that the vasicinone production in leaves (in vivo) was higher (0.047%; w/w ) in comparison to stem (in vivo) (0.027%; w/w ) of A. vasica , which supports our results where we found leaf samples to be the superior choice for vasicinone extraction than the other plant parts. Significant variation in vasicinone content was observed among in vitro leaf, callus and in vivo leaf; nonetheless, in vitro stem and in vivo stems yielded comparable quantities of vasicinone.…”
Section: Resultssupporting
confidence: 92%
“…The prime benefit of HPTLC is curtailment of time and cost per analysis (Dharmender et al 2010 ). Effective use of HPTLC has been well documented in some major economically important medicinal plants for their respective secondary metabolite assay (Gantait et al 2011 ; Swain et al 2012 ; Varghese et al 2013 ; Bala et al 2015 ; Kumar et al 2016 ; Shuayprom et al 2016 ), but only three reports are available on vasicinone quantification from in vivo plant samples of A. vasica (Das et al 2005 ; Suthar et al 2009 ; Roja et al 2011 ) with none on comparative quantification (between in vivo and in vitro plant parts) of vasicinone.…”
Section: Introductionmentioning
confidence: 99%
“…The anticestodal activity emerged from this study may be attributed due to the presence of two major alkaloids, vasicine and vasicinone and glycosides in Adhatoda vasica (Lateef et al, 2003;Das et al, 2005). Several studies have reported that plant secondary metabolites, particularly the alkaloids, glycosides, saponins and tannins are the active compounds which confer the antiparasitic effects of plants (Athanasiadou and Kyriazakis, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…The major constituents identified, however, are two alkaloids: vasicine and vasicinone (Das et al, 2005).…”
Section: Previously Isolated Class Of Constituentsmentioning
confidence: 98%
“…[24] An analytical study has also been developed by Das et al to determine these two alkaloids simultaneously using a simple high-performance thin-layer chromatographic method. [25] The distribution pattern of the alkaloids of AV has also been studied with change of season. [22] Apart from above analytical methods, a study was conducted to identify a method which extracts similar quality of total alkaloid obtained by the traditional method.…”
Section: Chemical Constituents and Evaluation Of Analytical Methodsmentioning
confidence: 99%